Inhibition of Escherichia coli-Induced Meningitis by Carboxyfullerence - Tsao, Nina (American Society for Microbiology, 1999)
The effect of a water-soluble malonic acid derivative of carboxyfullerence (C60) against Escherichia coli-induced meningitis was tested. C60 can protect the mice from E. coli-induced death in a dose-dependent manner. C60 administered intraperitoneally as late as 9 h after E. coli injection was still protective. The C60-treated mice had less tumor necrosis factor alpha and interleukin-1β production by staining of brain tissue compared to the levels of production for nontreated mice. The E. coli-induced increases in blood-brain barrier permeability and inflammatory neutrophilic infiltration were also inhibited. These data suggest that C60 is a potentially therapeutic agent for bacterial meningitis.